The Use of Souls: Souriau and Political Spirituality - Sjoerd van Tuinen (Aisthesis, 2023)
The body is at the heart of critical and phenomenological concerns, yet it is the soul that is increasingly under pressure. As we are being stripped of our structures of commonality, we need a renewed concept of political spirituality. My aim is to enrich Simondon’s concept of spirituality as transindividuality through Souriau’s transmodal architectonics. My argument proceeds in two steps: (i) I emphasize the precarious and communal modality of «having a soul», defining it as a possession without ownership and demonstrating its inseparability from the problems of intensive variation and discontinuity. (ii) I then argue that Souriau is inspired by Leibniz’s disjunction between the ontic soul and the relational body, which holds the key to an account of spiritual commitment that exceeds the union of corporeal and psychical existences insofar as it invents a new common use for them.